Sexual Health and Women Living With Spinal Cord Injury: The Unheard Voice - Piatt, Jennifer Ann; Simic Stanojevic, Ivanka; Stanojevic, Cedomir; Zahl, Melissa L.; Richmond, Mary Ann; Herbenick, Debra (Frontiers in Rehabilitation Sciences, 2022)
Women's sexual health within the context of sexual function and psychosocial dimensions while living with a spinal cord injury (SCI) has rarely been discussed separately from men living with a SCI or from a collective with other chronic conditions. To date, over 64,000 women in the U.S. are currently living with SCI, with total numbers increasing each year, as well as the demographics shifting to include more diversity in race and incidences occurring later in life. On average, SCI tends to be acquired during the childbearing years (~30 to 50 years old), as well as when women experience other health concerns associated with aging, including peri menopause and menopause. Additionally, women's sexual health is often conceptualized from the position of the absence of disease and dysfunction. However, consistent with the definitions furthered by the World Health Organization (WHO) and World Association of Sexual Health (WAS), we believe women's sexual health is multifaceted, moving beyond a focus on reproduction to also encompass sexual function and the psychosocial dimensions of sexual health both living with and without disabling conditions and disease. Within the lens, we present prior research that has been conducted, outcomes from these studies, implications for practice, and recommendations for future research. Thus the paper will expand the understanding of both sexual function and psychosocial dimensions for women living with SCI.